Amoxicillin treatment of experimental acute otitis media caused by Haemophilus influenzae with non-beta-lactamase-mediated resistance to beta-lactams: aspects of virulence and treatment. - Melhus, A (1997)
Through alterations primarily in the penicillin-binding proteins, a non-beta-lactamase-mediated resistance to beta-lactams has evolved in Haemophilus influenzae. The virulence of these chromosomally changed strains has been questioned. To ascertain whether these alterations involve a reduction in virulence of H. influenzae and whether they could be advantageous for the bacterium during amoxicillin treatment of acute otitis media, a total of 70 Sprague-Dawley rats were challenged with a susceptible recipient strain or a genetically similar resistant transformant strain. Antibiotic therapy was started on day 3 after inoculation, and the animals were monitored by daily otomicroscopy and analysis of bacterial samples from middle ear effusions obtained on day 8, the last day of observation. The animals were also sacrificed on days 4 and 8 and after 2 months for morphological examination. Compared with the susceptible recipient strain, recovery from infections caused by the resistant transformant strain was delayed, and the late structural changes were more severe in the animals challenged with the latter strain. The results of the study indicate that chromosomal alterations mediating a relatively low level of resistance to beta-lactams may be advantageous for H. influenzae during antibiotic treatment of a local infection in the rat, and the alterations may occur without any significant loss of virulence.